Prophylactic effects of Combretum molle boughs on changes in the hematological, biochemical, and histological parameters in dexamethasone-induced insulin-resistant rats - David Miaffo; Exodus Ntumah Ankang; Barthelemy Maidadi; Absalom Beram Gode (Elsevier, 2024)
Background: Combretum molle (Combretaceae) is a plant used in Cameroon traditional medicine to treat diabetes mellitus. To our knowledge, no studies have been performed on the preventive effects of C. molle on change in hematological, biochemical, and histological parameters of insulin-resistant rats. The aim of the study was to evaluate the preventive effect of C. molle on changes in the hematological biochemical, and histological parameters of insulin-resistant rats. Methods: Insulin resistance was induced for 10 days by subcutaneous injection of dexamethasone (1 mg/kg), one hour after oral pretreatment of animals with distilled water, metformin (40 mg/kg), and C. molle extract (250 and 500 mg/kg). Hematological profile (red blood cells, white blood cells, platelets and their indices), biomarkers of renal and hepatic function, hepatic glycogen level, activity of hepatic enzymes of carbohydrate metabolism, and histological sections of kidney, liver and pancreas were assessed. Results: C. molle extract (250 and 500 mg/kg) caused a significant decrease (p < 0.05 to p < 0.001) in white blood cells, platelets count, and the activities of fructose 6-diphosphatase, glucose-6-phosphate dehydrogenase, and transaminases. It also caused significant increase (p < 0.05 to p < 0.001) in red blood cells, hemoglobin, albumin, glycogen, urea, uric acid, and creatinine values, and fructose-1,6-diphospatase and glucokinase activity. Histological examination revealed regeneration of beta-cells of the pancreatic islets and preventive renal and hepatic tissues against damages caused by impact of dexamethasone. Conclusion: C. molle extract protected insulin-resistant patients from hematological, biochemical, and histopathological changes, there by validating the merits of the use of this plant in traditional medicine to treat diabetes mellitus and its complications.